Internal and external load profile during beach invasion sports match play by electronic performance and tracking systems: a systematic review - Vaccaro-Benet, P.; Gómez-Carmona, C. D.; Marzano-Felisatti, J. M.; Pino-Ortega, J. (Sensors, 2024)
Beach variants of popular sports like soccer and handball have grown in participation over the last decade. However, the characterization of the workload demands in beach sports remains limited compared to their indoor equivalents. This systematic review aimed to: (1) characterize internal and external loads during beach invasion sports match-play; (2) identify technologies and metrics used for monitoring; (3) compare the demands of indoor sports; and (4) explore differences by competition level, age, sex, and beach sport. Fifteen studies ultimately met the inclusion criteria. The locomotive volumes averaged 929 ± 269 m (average) and 16.5 ± 3.3 km/h (peak) alongside 368 ± 103 accelerations and 8 ± 4 jumps per session. The impacts approached 700 per session. The heart rates reached 166-192 beats per minute (maximal) eliciting 60-95% intensity. The player load was 12.5 ± 2.9 to 125 ± 30 units. Males showed 10-15% higher external but equivalent internal loads versus females. Earlier studies relied solely on a time-motion analysis, while recent works integrate electronic performance and tracking systems, enabling a more holistic quantification. However, substantial metric intensity zone variability persists. Beach sports entail intermittent high-intensity activity with a lower-intensity recovery. Unstable surface likely explains the heightened internal strain despite moderately lower running volumes than indoor sports. The continued integration of technology together with the standardization of workload intensity zones is needed to inform a beach-specific training prescription.